RECONSTRUCCIÓN DEL FRANQUISMO EN LA TELENOVELA AMAR EN TIEMPOS REVUELTOS MEDIANTE EL EMPLEO DE FUENTES DOCUMENTALES - Elisa REVUELTA ROJO (Fonseca, Journal of Communication, 2023)
Documentary sources have become in recent years an extremely useful tool in the historical televisive fiction in order to recreate the past, and in this article we analise which functions can have those sources and the way they contribute to recreate such a relevant historical period as Francoism in one of the most successful Spanish tv series: